Entre folhetins, filmes e minisséries: o processo adaptativo das obras A Dama do Lotação e Asfalto Selvagem de Nelson Rodrigues - Capelozi, Lays da Cruz (2022)
This thesis presents discussions about the works A Dama do Lotação, a chronicle belonging to the column A vida como ela é... and the novel Asfalto Selvagem: Engraçadinha – seus amores e seus pecados, both written by Nelson Rodrigues. These two works followed similar adaptive paths: first they were adapted by the cinematographic language, through the pornochanchada bias, and, later, they were adapted by the television language. Thus, in dialogue with Cultural History, it is our objective to analyze this adaptive process, taking into account the process of making each adaptation and reception..